The secret of Wildcat Swamp - Dixon, Franklin W. (New York Grosset & Dunlap, 1997)
An archaeological expedition in the West turns into a desperate attempt to capture robbers and an escaped convict.
Keywords: Hardy Boys (Fictitious characters) -- Fiction; Detective and mystery stories -- Juvenile fiction; Mystery fiction